The method development for controlling the mobile platform with four steering wheels - Nevlyudov, Igor; Novoselov, Sergiy; Sychova, Oksana; Zygin, Sergii (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject matter is a method for determining the robot trajectory with four steering wheels to reach a given point on a terrain map. The research goal is to develop a method for determining the orientation of the wheels depending on the trajectory of the mobile platform to increase the maneuverability of an autonomous robotic vehicle in a limited production space. Tasks to be solved: to analyze similar solutions, describe the proposed design of the steering unit mechanism for a mobile robotic cart, describe the kinematics of a mobile robot with four steerable wheels, develop an algorithm for the steering unit control module, propose a method for controlling a mobile platform with four steerable wheels, and perform experimental studies on the application of the proposed method. Scientific novelty: a method for determining the orientation of the wheels to reach a given point on the terrain plan has been proposed. An algorithm for performing calculations using a software tool has been developed. A mathematical justification for the method of controlling individual wheel blocks of a mobile platform has been provided. Methods of the study: modeling methods and automatic control theory, methods for describing linear dynamic systems, analytical modeling methods, computer modeling in the Matlab/Simulink environment. Results and conclusions: The mobile platform movement principle using four independent steering wheels is considered. A method for determining the orientation of the steering wheels depending on the trajectory of movement is proposed, which is based on the geometric analysis of the position of the platform and the target point, which allows calculating the angle of rotation of each wheel in such a way as to ensure movement to a given point without lateral slippage. A mathematical model of the control system is built, a structural and functional diagram is developed, an algorithm for processing commands, calculating the angles of rotation is described, and a three-level control system is implemented: linear speed, wheel orientation angle and angular speed of the entire platform. The developed mock-up sample of the mechatronic steering wheel assembly is described. The simulation conducted in the Simulink environment confirmed the operability of the proposed system.